The relationship between health literacy and general health of staff of Isfahan University of Medical Sciences - Azin Jafari; elahe tavassoli (Mashhad University of Medical Sciences, 2020)
Background and Objective: Health literacy is cognitive and social skills that determine the motivation and ability of individuals to access ،understand and use information in a way that maintains and improves their health.  Inadequate health literate people have a weaker health status. The aim of this study was to investigate the relationship between health literacy and health public of staff of Isfahan University of Medical Sciences. Materials and Methods: This descriptive-analytic and correlational study a total of 185 personnel staff in Isfahan University of medical sciences in 2019. Data collection tools were demographic information questionnaires, health literacy and general health. Data were analyzed by SPSS software version 22 using Descriptive and analytical tests. P-value less than 0.05 were considered significant. Results: 64.9% of the samples had sufficient health literacy.  In terms of general health, 52.4% of the research samples were at an Undesirable level. The findings showed that the relationship between health literacy and general health is significant (P-value=0/001). Conclusion: Regarding the communication of staff health literacy among staff units with their general health status, it is necessary Programs by effective institutions such as mental health centers, university counseling and human relations units To create job training to eliminate the necessary ambiguities or job stress before the start of the activity periodically or short-term courses held and the specialist forces to request more participation.